2011
DOI: 10.1371/journal.pone.0016760
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-3 Contributes to ZO-1 and Cl-5 Tight-Junction Disruption in Rapid Anoxic Neurovascular Unit Damage

Abstract: BackgroundTight-junction (TJ) protein degradation is a decisive step in hypoxic blood-brain barrier (BBB) breakdown in stroke. In this study we elucidated the impact of acute cerebral ischemia on TJ protein arrangement and the role of the apoptotic effector protease caspase-3 in this context.Methodology/Principal FindingsWe used an in vitro model of the neurovascular unit and the guinea pig whole brain preparation to analyze with immunohistochemical methods the BBB properties and neurovascular integrity. In bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 48 publications
(78 reference statements)
4
66
0
1
Order By: Relevance
“…In the current study, a significant upregulation of CD95 and activation of caspases-3 and 8, along with increased oxidative stress levels, may indicate activation of the extrinsic redoxsensitive machinery of apoptosis in the cerebrum after BPA treatment. Caspases-3 and 8 activation has been implicated in various neurodegenerative disorders [72]. The present results are in agreement with the finding that BPA exposure induces apoptosis and upregulation of Fas/ FasL and caspase-3 expression in the testes of mice [34].…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, a significant upregulation of CD95 and activation of caspases-3 and 8, along with increased oxidative stress levels, may indicate activation of the extrinsic redoxsensitive machinery of apoptosis in the cerebrum after BPA treatment. Caspases-3 and 8 activation has been implicated in various neurodegenerative disorders [72]. The present results are in agreement with the finding that BPA exposure induces apoptosis and upregulation of Fas/ FasL and caspase-3 expression in the testes of mice [34].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we have observed that hCMEC/D3 cells exposed to low cytokine concentrations increase effector caspase activation and ZO-1 delocalization in the absence of apoptosis. Indeed, Zehendner and colleagues (21) recently reported that in a model of the neurovascular unit, caspase-3 is strongly activated after 30 min of oxygen and glucose deprivation leading to ZO-1 and claudin-5 disorganization and barrier dysfunction associated with minimal DNA fragmentation. Disassembly of ZO-1 from the endothelial cell borders was not associated with changes in the total protein concentration, suggesting that TNF-a and IFN-g induced redistribution of ZO-1 rather than protein degradation.…”
Section: Discussionmentioning
confidence: 99%
“…However, caspase activation does not always lead to cell death (19), and it has been shown that hypoxia can induce caspase-9 and caspase-3 activation without apoptosis in neurons (20). Additionally, caspase-3 has been shown to be involved in ZO-1 and claudin-5 disassembly from the intercellular junctions independently of nuclear fragmentation during cerebral ischemia (21).…”
Section: B Lood-brain Barrier (Bbb) Dysfunction Is a Hallmark Of Neurmentioning
confidence: 99%
“…Quantitative densitometry analysis indicated that A 2A R level under hypoxia was 72% higher than that measured under normoxia. Apoptosis associated caspase-3 is an early marker of TJ disruption during acute cerebral ischemia [30]. Immunoblotting demonstrated a 186% increase of the active caspase-3 (17 kDa) in bEnd.3 cells under hypoxia, which implies the compromise of TJ tightness.…”
Section: Hypoxia Up-regulating a 2a R In Brain Capillary Endothelial mentioning
confidence: 97%